2011
DOI: 10.1038/ja.2010.164
|View full text |Cite
|
Sign up to set email alerts
|

Novel prodrugs of meropenem with two lipophilic promoieties: synthesis and pharmacokinetics

Abstract: To improve the oral absorption of meropenem (MEPM), we synthesized and evaluated a series of its double-promoiety prodrugs, in which lipophilic promoieties were introduced into carboxyl and pyrrolidinyl groups. Among these prodrugs, pivaloyloxymethyl (1R,5S,6S)-2-[(3S,5S)-5-(N,N-dimethylcarbamoyl)-1-(isobutyryloxymethyloxycarbonyl)pyrrolidin-3-ylthio]-6-[(1R)-1-hydroxyethyl]-1-methylcarbapen-2-em-3-carboxylate (4) and 1-ethylpropyloxycarbonyloxymethyl (1R,5S,6S)-2-[(3S,5S)-5-(N,N-dimethylcarbamoyl)-1-(isobutyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…carbamate prodrugs) could be used to slow the production of meropenem and this strategy has been explored previously. 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…carbamate prodrugs) could be used to slow the production of meropenem and this strategy has been explored previously. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Meropenem is a highly polar zwitterionic molecule (Log D < −2.5) 18 and unstable in aqueous conditions and must therefore be given intravenously within 3 hours following aqueous reconstitution. Aqueous degradation products are derived from β-lactam hydrolysis (major) and β-lactam dimerization (minor) via intermolecular attack of the pyrrolidine nitrogen onto the β-lactam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progression of infection in the wound microenvironment is avoided by the use of broad-spectrum antibiotics such as meropenem, which is a β-lactam antibiotic with a broad spectrum of activity. Due to its reduced oral absorption and short half-life, i.e., 0.75-1 h [26], meropenem requires multiple intravenous injections after short intervals, i.e., every 3 h after reconstitution [27]. To improve stability, bioavailability, [28], and patient compliance, a new drug-delivery system for effective meropenem delivery is required [29].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Cassano et al reported the synthesis of a new 5-amino salicylic acid (5-ASA) pro-prodrug, useful in Crohn disease treatment [11]. Recently in 2011, Tanaka et al improved the oral absorption of meropenem, where they synthesized and evaluated a series of its double-promoiety prodrugs, in which lipophilic promoieties were introduced into carboxyl and pyrrolidinyl groups [12]. In the present paper we synthesized a potential prodrug of dexamethasone conjugated with ibuprofen through a spacer arm amino acid (glycine).…”
Section: Introductionmentioning
confidence: 99%